The dual defensive strategy of Amorphophallus throughout its ontogeny. (3rd October 2017) - Liu, Kunpeng; Fadzly, Nik; Mansor, Asyraf; Zakaria, Rahmad; Ruppert, Nadine; Lee, Chow Yang
ABSTRACT: Amorphophallus bufo is a rarely studied plant in Malaysian tropical rainforests. We measured the spectral reflectance of different developmental stages of A. bufo (seedlings, juveniles and adults), background soil/ debris and leaves from other neighboring plant species. Results show that the leaves of A. bufo seedling have a similar reflectance curve as the background soil and debris. Adults and juveniles of A. bufo are similar to other neighboring plants' leaf colors. We hypothesize that the cryptic coloration of A. bufo seedlings plays an important role in camouflage and that the numerous black spots on the surface of the petioles and rachises, may serve as a defensive mimicry against herbivores.